Gear up your research guides with the emerging OPML codes. - Wilcox K (Computers in Libraries)
Outline Processor Markup Language is an emerging format that can allow you to create customized research packages to push to patrons. It's a way to gather collections of Web resources (links, RSS feeds, multimedia files), organize them as outlines, and publish them in a format that others can share and even subscribe to.